The grammatical conception of Joaquim Gonçalves: An analysis of his view on chinese word formation and classification - Li, Ling (2024)
This article delves into the grammatical perspective of Joaquim Afonso Gonçalves (1781-1841), a Portuguese Lazarist. The study focuses on his metalinguistic reflections as evident in his grammatical primer, Arte China (1829), designed for teaching Chinese to Europeans in 19th-century Macao. Specifically, this research centers on the grammatical references found in the third and fourth chapters of the manual, namely Grammatica and Syntaxe. It explores Gonçalves' observations regarding Chinese word formation and parts of speech, both perceived from a contrastive perspective. The analysis reveals that Gonçalves’ proposed word formation patterns are rooted in the morphological characteristics of Chinese words. Additionally, the parts of speech used to classify the Chinese lexicon not only inherit the Greek-Latin analytical and desctiptive model but also incorporate local traditions and embrace new categories to capture unique aspects of Chinese compared to his native language. This research seeks to illuminate Gonçalves’ grammatical conception, originally intended for direct disciples but potentially challenging for contemporary readers.